Clinical and pathological analyses of interstitial fibrosis and tubular atrophy cases after kidney transplantation. (July 2016) - Shimizu, Tomokazu; Toma, Hiroshi; Hayakawa, Nozomi; Shibahara, Rumi; Ishiyama, Ryou; Hayashida, Akihiro; Fujimori, Daiji; Tsunoyama, Kuniko; Ikezawa, Eri; Kitajima, Shoji; Iida, Shoichi; Ishida, Hideki; et al.
Abstract: Aim: We carried out a clinicopathological analysis of cases presenting with interstitial fibrosis and tubular atrophy (IF/TA) after renal transplantation in an attempt to clarify the mechanisms underlying the development and prognostic significance of IF/TA. Methods: IF/TA was diagnosed in 35 renal allograft biopsy specimens (BS) obtained from 35 renal transplant recipients under follow up at the Department of Transplant Surgery, Kidney Center, Toda Chuo General Hospital, between January 2014 and March 2015. Results: IF/TA was diagnosed at a median of 39.9 months after the transplantation. Among the 35 patients with IF/TA, 19 (54%) had a history of acute rejection. Among the 35 BS showing evidence of IF/TA, the IF/TA was grade I in 25, grade II in 9, and grade III in 1. Arteriosclerosis of the middle‐sized arteries was observed in 30 BS (86%). We then classified the 35 BS showing evidence of IF/TA according to their overall histopathological features, as follows; IF/TA alone (6 BS; 17%), IF/TA + medullary ray injury (12 BS; 34%), and IF/TA + rejection (12 BS; 34%). Loss of the renal allograft occurred during the observation period in one of the patients (3%). Of the remaining patients with functioning grafts, deterioration of the renal allograft function after the biopsies occurred in 15 patients (43%). Conclusions: The results of our study suggests that rejection contributes to IF/TA in 30–40% of cases, medullary ray injury in 30–40% of cases, and nonspecific injury in 20% of cases. IF/TA contributes significantly to deterioration of renal allograft function.